Generating a Novel Bispecific Nanobody to Enhance Antitumor Activity - Qiuhan Ge; Tianyuan Sun; Yanlin Bian; Xiaodong Xiao; Jianwei Zhu (Georg Thieme Verlag KG, 2020)
Tumor cells express high levels of human epidermal growth factor receptor 2 (HER2) and vascular endothelial growth factor receptor 2 (VEGFR2), which are closely related to their proliferation and survival. Cancer treatments that target a single signaling pathway may result in immune pathway escape or drug resistance. Based on the correlation between the HER2 and VEGFR2 signaling pathways, we speculated that targeting the two pathways simultaneously may produce a synergistic effect and avoid occurrence of drug resistance, resulting in improved efficacy. Anti-VEGFR2 nanobody 3VGR19-3 and anti-HER2 nanobody 2D3 were combined to construct a bispecific nanobody (Bi-Nb). They can recognize both HER2 and VEGFR2 (both highly expressed in HT-29 cells) to simultaneously block the two signaling pathways. We verified the affinity of the Bi-Nb to its targets using the surface plasmon resonance technology, and test its effects to inhibit tumor cell growth and promote cell apoptosis in vitro by the Cell Counting Kit-8 assay and apoptosis assay. In summary, we have successfully constructed a Bi-Nb, and verified its tumor-suppressing effects in vitro. Compared with a single monospecific nanobody, our Bi-Nb showed superior antitumor effect, which provides a new perspective for treatment of tumors with high HER2 and VEGFR2 expression.